Ambiguous Policies, Controversial Issues, and Strained Bureaucracies: Banning Critical Race Theory in Idaho - Luke Fowler; Jen Schneider (Journal of Social Equity and Public Administration)
Absent coping strategies, ambiguity strains administrative agencies and democratic institutions on multiple fronts, particularly where controversy is amplified by different ways of thinking that are incompatible with each other. This is examined using a case study of the implementation of Idaho’s House Bill 377 (HB377), the first state-level ban on “critical race theory” in public education in the United States. The brief and ambiguously written bill leaves a lot to be “figured out” by educators. Using a modified grounded theory approach, interviews with 10 faculty reveal how making sense of HB377 caused significant distress for faculty and strained their relationships with administrators. Findings suggest that this bill may have damaged higher education institutions in Idaho, particularly by creating low faculty morale among those teaching in areas newly perceived to be controversial. Conclusions consider implications for administrative agencies when faced with ambiguous laws and conflicting messages from elected officials.